Exploring the chances and challenges of green sukuk in Indonesia: TOWS method analysis - Yusrifalda, Amalia; Nurcahyo, Bimo (Journal of Law, Administration, and Social Science, 2025)
This study explores the opportunities and challenges of green sukuk in Indonesia through a comprehensive TOWS method analysis. By reviewing existing literature and conducting IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary), the study identifies the internal strengths and weaknesses, as well as external opportunities and threats, affecting the green sukuk market in Indonesia. The findings suggest that an aggressive SO (Strength-Opportunity) strategy is most suitable for leveraging the country's strong government support and positive market response, while capitalizing on the increasing global demand for sustainable investments. The study recommends enhancing public and investor awareness, strengthening regulatory support, fostering collaborations with global financial institutions, and providing incentives for green projects. These strategic actions are essential for maximizing the potential of green sukuk as a sustainable financing instrument, driving Indonesia's economic growth, and reinforcing its leadership in the global Islamic finance market. This research contributes to the ongoing discourse on Islamic finance and green financing, offering strategic insights and recommendations for policymakers, investors, and stakeholders to advance Indonesia's environmental and economic goals.